Silicon carbide particle reinforced aluminum matrix composite plate strip and preparation method thereof

By combining copper plating on the surface of silicon carbide particles and electromagnetic stirring with a continuous extrusion process, the problems of high cost, edge cracks, low efficiency and uneven distribution in the production of aluminum-based silicon carbide composite strips are solved, achieving high quality, low cost Cost-effective and efficient production.

CN119351831APending Publication Date: 2025-01-24广州众山功能材料有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556466.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The production process of existing aluminum-based silicon carbide composite sheet strips has problems such as high cost, edge cracking problems, low production efficiency and uneven distribution of silicon carbide particles, which is difficult to meet the needs of high performance, low cost and high efficiency.

Method used

Copper plating treatment and electromagnetic stirring methods of silicon carbide particles are used to combine continuous squeezing processes to eliminate the heating process in traditional squeezing, use the frictional heat mechanism for heat processing, and prepare high -quality aluminum -based silicon carbide composite materials.

Benefits of technology

The high -quality production of aluminum -based silicon carbide composite materials has been realized, the energy consumption and production costs are reduced, the uniformity and mechanical properties of production efficiency and materials are improved. The material utilization rate can reach more than 97%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351831A_ABST
    Figure CN119351831A_ABST
Patent Text Reader

Abstract

The invention provides a silicon carbide particle reinforced aluminum matrix composite plate strip and a preparation method thereof, and relates to the technical field of aluminum matrix composites.The silicon carbide particle reinforced aluminum matrix composite plate strip comprises, by mass, 10-25% of mixed powder and 75-90% of an aluminum alloy matrix; wherein the mixed powder comprises copper-plated silicon carbide particles and aluminum powder. According to the method, continuous extrusion depends on the friction heat generation mechanism, the heating process in a traditional extrusion technology is omitted, the heating equipment investment and the energy cost are saved, various advantages of a hot working technology are still kept, and the aluminum-based silicon carbide composite material plate with the high quality requirement can be prepared; the energy consumption of the continuous extruder can be reduced by more than 30% compared with the traditional extrusion, and the production efficiency is far higher than that of the traditional extrusion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum-based composite materials, and in particular to a silicon carbide particle reinforced aluminum-based composite material strip and a preparation method thereof. Background Art

[0002] Aluminum silicon carbide composites are widely used in aerospace, transportation and other fields as lightweight structural materials. They can replace aluminum alloys, cast steel, cast iron, titanium alloys and other materials. In recent years, with the rapid development of domestic aerospace, automobile and electronics industries, the demand for aluminum-based silicon carbide composites is increasing year by year. Representative parts are brake parts, pistons, connecting rods, and foil structural parts for 3C products such as automotive plates, tablet computers and mobile phones.

[0003] At present, the main production methods of aluminum-based silicon carbide composite materials are powder metallurgy ingots combined with traditional extrusion, stirring casting combined with traditional extrusion, and casting and rolling into plates. The powder metallurgy method mainly produces aluminum-based silicon carbide composite material blanks by powder metallurgy, and then produces plates and strips by extrusion and traditional extrusion. The main problem with this process is that the cost of powder metallurgy production is too high, the plates and strips are prone to edge cracking during the extrusion process, and the efficiency of traditional extrusion mass production is low; the stirring casting method mainly uses stirring casting to form aluminum-based silicon carbide composite blanks, and then produces aluminum-based silicon carbide composite material blanks by traditional extrusion and extrusion. The cost and efficiency of stirring casting and rolling of this process are still relatively high. Due to the discontinuity of the blanks and the difficulty of extruding aluminum-based silicon carbide composite materials, the efficiency and continuous production of traditional extrusion are low. The production capacity is low; the casting and rolling method mainly extrudes the slab directly from the liquid solidification process after smelting. The main problem of this process is that the silicon carbide particles cannot be evenly distributed during the smelting and casting and rolling process, resulting in very uneven distribution of silicon carbide particles inside the cast and rolled slab. There is no subsequent extrusion process to improve the microstructure distribution of silicon carbide. At the same time, silicon carbide will react with aluminum liquid at the interface if the surface is not treated during the casting process, resulting in relatively unstable microstructure and performance of the slab directly extruded. The above production methods result in the production of aluminum-based silicon carbide sheets that cannot meet the high performance, low cost and high efficiency requirements of automobiles and 3C consumer electronics. Summary of the invention

[0004] The purpose of the present invention is to provide a silicon carbide particle reinforced aluminum-based composite material plate and a preparation method thereof. Through continuous extrusion relying on the friction heat generation mechanism, the heating process in the traditional extrusion process is eliminated, saving the investment in heating equipment and energy costs, but still retaining the various advantages of the hot processing process, and aluminum-based silicon carbide composite material plates with high quality requirements can be prepared. The continuous extruder can reduce energy consumption by more than 30% compared with traditional extrusion, and the production efficiency is much higher than traditional extrusion.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a silicon carbide particle reinforced aluminum-based composite material plate strip, which comprises 10-25% of mixed powder and 75-90% of aluminum alloy matrix by mass percentage;

[0007] Wherein, the mixed powder includes copper-plated silicon carbide particles and aluminum powder.

[0008] Furthermore, based on the above technical solution, the mass ratio of the copper-plated silicon carbide particles to the aluminum powder is (5-10):1.

[0009] Further, based on the above technical solution, the size of the silicon carbide particles that have not been copper plated is 3-20 μm;

[0010] The size of aluminum powder is 1-10μm;

[0011] And / or, the aluminum alloy substrate is an aluminum alloy ingot.

[0012] The present invention also provides a method for preparing the above silicon carbide particle reinforced aluminum-based composite material strip, comprising the following steps:

[0013] S1: performing copper plating treatment on the surface of silicon carbide particles to obtain copper-plated silicon carbide particles;

[0014] S2: pre-treating the copper-plated silicon carbide particles and aluminum powder by mixing and dispersing to obtain a mixed powder;

[0015] S3: melting the aluminum alloy ingot to obtain aluminum liquid, adding the mixed powder into the aluminum liquid for stirring, and then obtaining a round wire rod through a horizontal continuous casting process;

[0016] S4: homogenizing the round wire rod and then peeling the round wire rod; cleaning and drying the peeled round wire rod, and then continuously extruding the strip to obtain a silicon carbide particle reinforced aluminum-based composite material plate.

[0017] Further, on the basis of the above technical solution, in step S1, the copper plating process includes the following steps:

[0018] S11: degreasing the silicon carbide particles and washing them with water for multiple times to obtain clean silicon carbide particles;

[0019] S12: sequentially subjecting the cleaned silicon carbide particles to acid activation, palladium catalyst layer deposition and chemical copper plating to obtain copper-plated silicon carbide particles.

[0020] Further, on the basis of the above technical solution, the acid activation is to immerse the clean silicon carbide particles in a hydrochloric acid solution;

[0021] Wherein, the concentration of the hydrochloric acid solution is 45-55%, and the acid activation time is 20-30min;

[0022] And / or, the depositing of the palladium catalyst layer refers to washing the silicon carbide after acid activation treatment and then immersing it in palladium water;

[0023] Wherein, the palladium water comprises 5-15 ppm of colloidal palladium and 45-55% hydrochloric acid solution;

[0024] The volume ratio of colloidal palladium to hydrochloric acid solution is 1:(1-2);

[0025] The immersion time in palladium water is 30-50 minutes;

[0026] And / or, the chemical copper plating refers to immersing the silicon carbide particles deposited with the palladium catalyst layer in a chemical copper plating solution;

[0027] Wherein, the chemical copper plating solution comprises 3-7 g / L copper sulfate, 5-15% formaldehyde, 20-30 g / L potassium sodium tartrate and 0-5 g / L EDTA-2Na;

[0028] The immersion time in the chemical copper plating solution is 30-50 minutes.

[0029] Furthermore, based on the above technical solution, in step S2, the mass ratio of the copper-plated silicon carbide particles to the aluminum powder is (10-15):1.

[0030] Further, based on the above technical solution, step S3 specifically includes the following steps:

[0031] S31: placing the aluminum alloy ingot in a smelting furnace for melting, and cooling the ingot after it is completely melted into aluminum liquid to obtain aluminum liquid;

[0032] S32: introducing argon gas to stir and degas the aluminum liquid, then adding a slag remover to perform refining and slag removal, and standing to cool down;

[0033] S33: placing the mixed powder in the cooled aluminum liquid for stirring and filtering, placing the filtrate in a crystallizer for horizontal continuous casting, and obtaining a round wire rod.

[0034] Further, on the basis of the above technical solution, in step S31, the melting temperature is 750-770°C; after the aluminum ingot is completely melted into aluminum liquid, the temperature is lowered to 720-740°C;

[0035] And / or, in step S32, the degassing time is 20-30 min, and the stirring speed is 300-400 r / min;

[0036] In step S32, the mass ratio of aluminum liquid to slag remover is 450-550:1;

[0037] The slagging agent includes one or more of potassium chloride, sodium chloride, sodium fluoride or calcium fluoride;

[0038] In step S32, the temperature is cooled to 630-660°C for 10-20 minutes.

[0039] And / or, in step S33, the stirring refers to stirring for 10-20 min by an electromagnetic stirring device;

[0040] The crystallizer is a 10-head crystallizer, the height of the effective crystallization zone of the crystallizer is 10-20 mm, the cooling water inlet temperature is ≤25°C, the outlet water temperature is ≤45°C, the water pressure is 0.01-0.03Mpa, and the horizontal continuous casting speed is 850-950mm / min;

[0041] The diameter of the round wire rod is 10-15mm.

[0042] Further, based on the above technical solution, step S4 specifically includes the following steps:

[0043] S41: performing homogenization treatment on the round wire rod;

[0044] S42: peeling the round wire rod after the homogenization treatment;

[0045] S43: The peeled round wire rod is cleaned and dried, and then extruded into a silicon carbide particle reinforced aluminum-based composite material plate and strip through a continuous extruder.

[0046] Further, on the basis of the above technical solution, in step S41, the temperature of the homogenization treatment is 500-550°C and the time is 2-4h;

[0047] and / or, in step S42, the peeling speed is 16-18 m / min;

[0048] And / or, in step S43, the continuous extrusion temperature is between 400-450°C, and the extrusion wheel speed is 10-20rpm.

[0049] The present invention provides a silicon carbide particle reinforced aluminum-based composite material strip and a preparation method thereof, and the beneficial effects are as follows:

[0050] (1) The present invention ensures that the interface of the cast aluminum-based silicon carbide material is well bonded and the silicon carbide particles are relatively evenly distributed by copper plating pretreatment on the surface of the silicon carbide particles and electromagnetic stirring;

[0051] (2) The present invention relies on the friction heat generation mechanism through continuous extrusion, eliminating the heating process in the traditional extrusion process, saving the investment in heating equipment and energy costs, but still retains the various advantages of the thermal processing process, and can prepare aluminum-based silicon carbide composite material plates with high quality requirements. The continuous extruder can reduce energy consumption by more than 30% compared with traditional extrusion, and the production efficiency is much higher than that of traditional extrusion.

[0052] (3) The present invention realizes uninterrupted continuous production and can even produce aluminum-based silicon carbide strips of infinite length; and the equipment has a high degree of automation during the continuous production process, and the number of operators is small, which greatly reduces the labor cost. At the same time, it also greatly reduces the extrusion residues, head and tail cutting and other waste materials in traditional extrusion, and the material utilization rate can reach more than 97%. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0054] Figure 1 A schematic flow chart of a method for preparing a silicon carbide particle reinforced aluminum-based composite material strip provided by the present invention;

[0055] Figure 2 The internal organization diagram of the silicon carbide particle reinforced aluminum-based composite material strip provided by the present invention;

[0056] icon:

[0057] 1. Wire pay-off machine; 2. Billet straightener; 3. Ultrasonic machine; 4. Continuous casting extruder; 5. Holding furnace; 6. Wire take-up machine. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0059] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0060] According to a first aspect of the present invention, there is provided a silicon carbide particle reinforced aluminum-based composite material strip, comprising, by mass percentage, 10-25% (e.g., 12%, 14%, 16%, 18%, 20%, 22%, 24%, etc.) of a mixed powder and 75-90% (e.g., 80%, 82%, 84%, 86%, 88%, etc.) of an aluminum alloy matrix;

[0061] Wherein, the mixed powder includes copper-plated silicon carbide particles and aluminum powder.

[0062] Specifically, the present invention uses copper plating on the surface of silicon carbide particles, and the copper plating layer not only significantly improves the wettability and interfacial bonding between the silicon carbide particles and the aluminum matrix, but also promotes the mutual penetration and diffusion of the two in a molten state. And in the casting process, the copper-plated silicon carbide particles are evenly dispersed and embedded in the aluminum matrix due to the intermediary effect of the copper plating layer, and the dispersibility of the silicon carbide particles is significantly improved, effectively avoiding the common particle agglomeration phenomenon in traditional casting methods. This not only makes the distribution of silicon carbide particles in the aluminum matrix more uniform, but also greatly increases the overall mechanical properties and thermal stability of the composite material.

[0063] As an optional embodiment of the present invention, the mass ratio of the copper-plated silicon carbide particles to the aluminum powder is (5-10):1 (such as 6:1, 7:1, 8:1, 9:1, etc.).

[0064] Specifically, by mixing copper-plated silicon carbide particles and aluminum powder at a mass ratio of (5-10): 1, the dispersibility of copper-plated silicon carbide particles in aluminum liquid can be further effectively improved to avoid the phenomenon of silicon carbide agglomeration. If the aluminum powder content is too much, it will occupy more space, so that the relative proportion of copper-plated silicon carbide particles in the mixture is reduced, thereby increasing the chance of contact and agglomeration between particles, resulting in a decrease in the dispersibility of copper-plated silicon carbide particles in aluminum liquid, and ultimately affecting the uniformity and mechanical properties of the composite material.

[0065] As an optional embodiment of the present invention, the size of the silicon carbide particles that have not been copper plated is 3-20 μm (such as 5 μm, 10 μm, 15 μm, etc.);

[0066] The size of aluminum powder is 1-10μm (such as 2μm, 4μm, 6μm, 8μm, etc.);

[0067] And / or, the aluminum alloy substrate is an aluminum alloy ingot.

[0068] According to a second aspect of the present invention, there is provided a method for preparing the silicon carbide particle reinforced aluminum-based composite material strip as described above, comprising the following steps:

[0069] S1: performing copper plating treatment on the surface of silicon carbide particles to obtain copper-plated silicon carbide particles;

[0070] S2: performing a powder mixing and dispersion pretreatment on the copper-plated silicon carbide particles and the aluminum powder to obtain a mixed powder;

[0071] S3: melting the aluminum alloy ingot to obtain aluminum liquid, adding the mixed powder into the aluminum liquid for stirring, and then obtaining a round wire rod through a horizontal continuous casting process;

[0072] S4: homogenizing the round wire rod and then peeling the round wire rod; cleaning and drying the peeled round wire rod, and then continuously extruding the strip to obtain a silicon carbide particle reinforced aluminum-based composite material plate.

[0073] like Figure 1 As shown, it is a schematic flow chart of the method for preparing the silicon carbide particle reinforced aluminum-based composite material strip provided by the present invention. The round wire rod passes through the wire pay-off machine 1 and is fed into the billet straightener 2. The round wire rod is cleaned by the ultrasonic machine 3 and enters the continuous casting extruder 4 for continuous extrusion. Finally, the extruded strip product is wound up by a constant tension winding device. The die mouth is ensured to be equipped with a heat preservation furnace 5. The furnace temperature is controlled at 300-400°C. Finally, the strip of silicon carbide particle reinforced aluminum-based composite material strip is obtained after being wound up by the wire take-up machine 6.

[0074] Specifically, the present invention generates a large amount of heat energy through continuous mechanical deformation of the round wire rod obtained by peeling in a continuous extrusion operation mode in a closed mold system. The heat energy just meets the conditions required for the composite material to form a stable bond at high temperature. Therefore, effective plasticization and uniform mixing of the material can be achieved without additional heating equipment, thereby saving energy while retaining many advantages of the thermal processing technology that bestows the material, such as enhancing the interface bonding strength between the particles and the matrix metal, improving the overall mechanical properties and thermal stability of the material, etc., to prepare aluminum-based silicon carbide composite material plates that meet high quality requirements.

[0075] Moreover, the method for preparing the silicon carbide particle reinforced aluminum-based composite material strip provided by the present invention can reduce energy consumption by more than 30% compared with the traditional processing method. This significant improvement is mainly due to the efficient conversion and utilization of energy during the continuous extrusion process, which reduces the loss of energy during transmission and conversion. In addition, continuous extrusion also greatly improves production efficiency. Through uninterrupted automated operation processes, it reduces waiting time and labor costs in the production cycle, greatly increases product output speed, and meets the rapidly growing market demand for high-quality aluminum-based silicon carbide composite material plates.

[0076] The present invention realizes uninterrupted continuous production and can even produce aluminum-based silicon carbide strips of infinite length; and the equipment has a high degree of automation during the continuous production process, and fewer operators are required, which greatly reduces labor costs. At the same time, it also greatly reduces waste such as extrusion residues, head and tail cuttings in traditional extrusion, and the material utilization rate can reach more than 97%.

[0077] As an optional embodiment of the present invention, in step S1, the copper plating process includes the following steps:

[0078] S11: degreasing the silicon carbide particles and washing them with water for multiple times to obtain clean silicon carbide particles;

[0079] S12: sequentially subjecting the cleaned silicon carbide particles to acid activation, palladium catalyst layer deposition and chemical copper plating to obtain copper-plated silicon carbide particles.

[0080] Specifically, the degreasing operation is to use silicon carbide cleaning agent and ultrasonic cleaning in sequence to remove oil stains on the surface of silicon carbide; water washing is to place silicon carbide particles in flowing pure water and remove surface residues by repeated rinsing.

[0081] As an optional embodiment of the present invention, the acid activation is to soak the clean silicon carbide particles in a hydrochloric acid solution;

[0082] The concentration of the hydrochloric acid solution is 45-55% (such as 17%, 50%, 53%, etc.), and the acid activation time is 20-30 minutes (such as 22 minutes, 24 minutes, 26 minutes, 28 minutes, etc.).

[0083] Specifically, a hydrochloric acid solution with a concentration of 45-55% can ensure that impurities and oxides on the surface of silicon carbide can be effectively removed without causing excessive corrosion to the silicon carbide itself. A concentration that is too low may not achieve the expected activation effect, while a concentration that is too high may cause excessive corrosion of the silicon carbide surface, affecting the quality of subsequent treatment.

[0084] Furthermore, the length of activation time will directly affect the roughness and activity of the silicon carbide surface, and thus affect the adhesion and quality of subsequent plating or coating. Too short an activation time may not fully activate the silicon carbide surface, while too long an activation time may cause the surface to be excessively rough or produce other adverse effects.

[0085] As an optional embodiment of the present invention, the depositing of the palladium catalyst layer refers to washing the silicon carbide after acid activation treatment and then immersing it in palladium water;

[0086] Wherein, the palladium water includes 5-15ppm (such as 7ppm, 9ppm, 11ppm, 13ppm, etc.) of colloidal palladium and 45-55% (such as 17%, 50%, 53%, etc.) of hydrochloric acid solution;

[0087] The volume ratio of colloidal palladium to hydrochloric acid solution is 1:(1-2) (e.g. 1:1, 1:1.5, 1:1.7, 1:2, etc.);

[0088] The soaking time in palladium water is 30-50 minutes (such as 35 minutes, 40 minutes, 45 minutes, etc.).

[0089] As an optional embodiment of the present invention, the chemical copper plating refers to immersing the silicon carbide particles deposited with the palladium catalyst layer in a chemical copper plating solution;

[0090] Wherein, the chemical copper plating solution includes 3-7g / L (such as 4g / L, 5g / L, 6g / L, etc.) of copper sulfate, 5-15% (such as 7%, 9%, 11%, 13%) of formaldehyde, 20-30g / L (such as 22g / L, 24g / L, 26g / L, 28g / L, etc.) of potassium sodium tartrate and 0-5g / L (such as 1g / L, 2g / L, 3g / L, 4g / L, etc.) of EDTA-2Na;

[0091] The immersion time in the chemical copper plating solution is 30-50 minutes (such as 35 minutes, 40 minutes, 45 minutes, etc.).

[0092] As an optional implementation of the present invention, step S3 specifically includes the following steps:

[0093] S31: placing the aluminum alloy ingot in a smelting furnace for melting, and cooling the ingot after it is completely melted into aluminum liquid to obtain aluminum liquid;

[0094] S32: introducing argon gas to stir and degas the aluminum liquid, then adding a slag remover to perform refining and slag removal, and allowing the liquid to stand for cooling;

[0095] S33: placing the mixed powder in the cooled aluminum liquid for stirring and filtering, placing the filtrate in a crystallizer for horizontal continuous casting, and obtaining a round wire rod.

[0096] As an optional embodiment of the present invention, in step S31, the melting temperature is 750-770°C (such as 755°C, 760°C, 765°C, etc.); after the aluminum ingot is completely melted into aluminum liquid, the temperature is lowered to 720-740°C (such as 725°C, 730°C, 735°C, etc.);

[0097] In step S32, the degassing time is 20-30 min (e.g., 22 min, 24 min, 26 min, 28 min, etc.), and the stirring speed is 300-400 r / min (e.g., 320 r / min, 340 r / min, 360 r / min, 380 r / min, etc.);

[0098] In step S32, the mass ratio of aluminum liquid to slag remover is 450-550:1 (e.g., 470:1, 490:1, 510:1, 530:1, etc.);

[0099] The slagging agent includes one or more of potassium chloride, sodium chloride, sodium fluoride or calcium fluoride;

[0100] In step S32, the cooling time is 10-20 minutes (such as 12 minutes, 14 minutes, 16 minutes, 18 minutes, etc.); the temperature is lowered to 630-660°C (640°C, 650°C, etc.);

[0101] In step S33, the stirring refers to stirring for 10-20 min (e.g., 2 min, 4 min, 6 min, 8 min, etc.) by electromagnetic stirring equipment;

[0102] The crystallizer is a 10-head crystallizer, the height of the effective crystallization zone of the crystallizer is 10-20 mm (such as 12 mm, 14 mm, 16 mm, 18 mm, etc.), the cooling water inlet temperature is ≤25°C (such as 20°C, 21°C, 22°C, 23°C, 24°C, etc.), the outlet water temperature is ≤45°C (such as 40°C, 41°C, 42°C, 43°C, 44°C, etc.), the water pressure is 0.01-0.03Mpa (such as 0.015Mpa, 0.02Mpa, 0.025Mpa, etc.), and the horizontal continuous casting speed is 850-950mm / min (such as 870mm / min, 890mm / min, 910mm / min, 930mm / min, etc.);

[0103] The diameter of the round wire rod is 10-15mm (such as 11mm, 12mm, 13mm, 14mm, etc.).

[0104] Specifically, the advantages of using electromagnetic stirring equipment in the horizontal continuous casting process are mainly reflected in the following aspects:

[0105] (1) Improve the quality of castings:

[0106] Electromagnetic stirring can improve the internal structure and component distribution of the ingot, reduce defects such as central segregation, looseness and shrinkage, thereby improving the strength and toughness of the ingot; through electromagnetic stirring, the flow of molten steel inside the ingot can be made more uniform, the formation of equiaxed crystals can be promoted, and the grains can be refined, thereby improving the mechanical properties of the ingot; and electromagnetic stirring helps to float and remove inclusions and gases in the molten steel, improve the purity of the molten steel, and further improve the quality of the ingot.

[0107] (2) Improve production efficiency:

[0108] Electromagnetic stirring can accelerate the flow and heat transfer process of molten steel, allowing liquid steel to reach solidification conditions faster, thereby shortening the residence time of liquid steel in the casting machine and improving production efficiency.

[0109] (3) Improve production safety:

[0110] Electromagnetic stirring can improve the temperature distribution inside the ingot, reduce the thermal stress caused by excessive temperature gradient, and reduce the risk of ingot cracking; and electromagnetic stirring realizes automatic control, reduces manual intervention, reduces the labor intensity of operators, and improves the safety of the production environment.

[0111] (4) Energy saving and environmental protection:

[0112] Compared with traditional stirring methods, electromagnetic stirring reduces mechanical wear and energy loss due to its contactless conversion feature; and by improving the quality of the ingot, it reduces waste caused by defects, which is beneficial to resource conservation and environmental protection.

[0113] As an optional implementation of the present invention, step S4 specifically includes the following steps:

[0114] S41: performing homogenization treatment on the round wire rod;

[0115] S42: peeling the round wire rod after the homogenization treatment;

[0116] S43: The peeled round wire rod is cleaned and dried, and then extruded into a silicon carbide particle reinforced aluminum-based composite material plate and strip through a continuous extruder.

[0117] As an optional embodiment of the present invention, in step S41, the temperature of the homogenization treatment is 500-550° C. (such as 510° C., 520° C., 530° C., 540° C., etc.), and the time is 2-4 h (such as 2.5 h, 3 h, 3.5 h, etc.);

[0118] and / or, in step S42, the peeling speed is 16-18 m / min (e.g., 16.5 m / min, 17 m / min, 17.5 m / min, etc.);

[0119] And / or, in step S43, the continuous extrusion temperature is between 400-450°C (for example, 410°C, 420°C, 430°C, 440°C, etc.), and the extrusion wheel speed is 10-20rpm (for example, 11rpm, 12rpm, 13rpm, 14rpm, 15rpm, 16rpm, 17rpm, 18rpm, 19rpm, etc.).

[0120] Specifically, the continuous extrusion temperature in step S43 is limited to 400-450°C, which is lower than the traditional continuous heating temperature of the aluminum substrate. This is because heat energy will be generated due to friction during the continuous extrusion process. This heat energy will increase the temperature to 500-550°C, reaching the optimal extrusion temperature of the aluminum substrate, which can not only ensure that the aluminum substrate has good plasticity, but also avoid melting or other problems caused by overheating.

[0121] If the temperature set for continuous extrusion is too high, coupled with frictional heat, the temperature of the aluminum matrix may rise significantly, even exceeding its melting point, resulting in partial or complete melting, making it impossible to complete the extrusion into plates and strips; excessively high temperatures may also cause the coarsening of the internal structure of the aluminum matrix, reducing its mechanical properties and processing performance.

[0122] If the temperature set for continuous extrusion is too low, even taking into account the heat generated by friction, the temperature of the aluminum substrate may not reach the ideal extrusion temperature, resulting in reduced plasticity of the aluminum substrate during the extrusion process, increased extrusion force, and even defects such as cracks. Too low a temperature may also affect the overall efficiency of the production line because it takes longer to heat the aluminum substrate to the appropriate temperature.

[0123] Specifically, the extrusion wheel speed of 10-20rpm is a relatively slow speed range. The lower speed helps to control the flow and deformation process of the material and reduce the stress and defects caused by high-speed extrusion. Slow extrusion also helps to ensure that the material is fully heated and evenly distributed during the extrusion process, thereby improving the quality and consistency of the product.

[0124] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0125] Example 1

[0126] S1: placing silicon carbide particles (average particle size of 10 μm) in a silicon carbide cleaning agent for preliminary cleaning for 20 minutes, then ultrasonically cleaning for 30 minutes, placing the silicon carbide particles in flowing pure water, and repeatedly rinsing to remove surface residues to obtain clean silicon carbide particles;

[0127] The cleaned silicon carbide particles were immersed in a 55% hydrochloric acid solution for 20 minutes for acid activation;

[0128] After the acid-activated silicon carbide was washed with pure water several times, it was immersed in palladium water for 30 minutes.

[0129] The palladium water includes 10 ppm colloidal palladium and 55% hydrochloric acid solution, and the volume ratio of the colloidal palladium to the hydrochloric acid solution is 1:1;

[0130] The silicon carbide particles on which the palladium catalyst layer is deposited are immersed in a chemical copper plating solution for 30 minutes, and after the immersion is completed, they are washed with pure water for multiple times to obtain copper-plated silicon carbide particles;

[0131] The chemical copper plating solution includes 5 g / L copper sulfate, 10% formaldehyde, 25 g / L potassium sodium tartrate and 2 g / L EDTA-2Na.

[0132] S2: Pre-treating the copper-plated silicon carbide particles (20 kg) and aluminum powder (4 kg, with an average particle size of 5 μm) by mixing and dispersing at a mass ratio of 5:1 to obtain 24 kg of mixed powder;

[0133] S3: Weigh 76 kg of aluminum alloy ingot, place the aluminum alloy ingot in a melting furnace, melt it at 770° C., and after the aluminum ingot is completely melted into aluminum liquid, cool it to 740° C. to obtain aluminum liquid;

[0134] Argon gas was introduced to stir and degas the aluminum liquid for 30 minutes at a stirring speed of 400 r / min, and then 152 g of slag remover sodium chloride was added for refining and deslagging. The mixture was allowed to stand for 20 minutes and then cooled to 660°C.

[0135] Among them, the mass ratio of aluminum liquid to slag remover is 500:1;

[0136] 24 kg of mixed powder was placed in the cooled aluminum liquid and stirred by electromagnetic stirring equipment for 20 minutes and filtered. The filtrate was placed in a 10-head crystallizer for horizontal continuous casting. The effective crystallization zone height of the crystallizer was 15 mm, the cooling water inlet temperature was 25 ° C, the outlet water temperature was 40 ° C, the water pressure was 0.02 MPa, and the horizontal continuous casting speed was 900 mm / min to obtain round wire rods with a diameter of 12 mm.

[0137] S4: homogenizing the round wire rod at 540°C for 3h;

[0138] The round wire rod after homogenization is subjected to peeling at a peeling speed of 17 m / min;

[0139] The peeled round wire rod is cleaned and dried, and then extruded into plates and strips through a continuous extruder. The continuous extrusion temperature is controlled at 420°C, and the extrusion wheel speed is 15rpm. Finally, the extruded plate and strip products are rolled up using a constant tension winding device. The die mouth is equipped with a heat preservation furnace, and the furnace temperature is controlled at 350°C. Finally, after rolling, a coil of aluminum-based silicon carbide composite material is obtained.

[0140] like Figure 2 As shown, this is the internal organization diagram of the plate and strip of aluminum-based silicon carbide composite material. From the figure, it can be seen that silicon carbide can be evenly distributed in the aluminum matrix without agglomeration or the like.

[0141] Example 2

[0142] S1: placing silicon carbide particles (average particle size of 15 μm) in a silicon carbide cleaning agent for preliminary cleaning for 20 minutes, then ultrasonically cleaning for 30 minutes, placing the silicon carbide particles in flowing pure water, and repeatedly rinsing to remove surface residues to obtain clean silicon carbide particles;

[0143] The cleaned silicon carbide particles were immersed in a 50% hydrochloric acid solution for 30 minutes for acid activation;

[0144] After the acid-activated silicon carbide was washed several times with pure water, it was immersed in palladium water for 40 minutes.

[0145] The palladium water includes 15 ppm colloidal palladium and 50% hydrochloric acid solution, and the volume ratio of the colloidal palladium to the hydrochloric acid solution is 1:1;

[0146] The silicon carbide particles on which the palladium catalyst layer is deposited are immersed in a chemical copper plating solution for 30 minutes, and after the immersion is completed, they are washed with pure water for multiple times to obtain copper-plated silicon carbide particles;

[0147] The chemical copper plating solution includes 7 g / L copper sulfate, 15% formaldehyde, 30 g / L potassium sodium tartrate and 5 g / L EDTA-2Na.

[0148] S2: Pre-treatment of mixing and dispersing the copper-plated silicon carbide particles (20 kg) and aluminum powder (2 kg, with an average particle size of 7 μm) at a mass ratio of 10:1 to obtain 22 kg of mixed powder;

[0149] S3: Weigh 78 kg of aluminum alloy ingot, place the aluminum alloy ingot in a melting furnace, melt it at 750° C., and after the aluminum ingot is completely melted into aluminum liquid, cool it to 720° C. to obtain aluminum liquid;

[0150] Argon was introduced to stir and degas the aluminum liquid for 30 minutes at a stirring speed of 350 r / min, and then 156 g of slag removal agent potassium chloride was added for refining and deslagging. The mixture was allowed to stand for 20 minutes and then cooled to 650°C.

[0151] Among them, the mass ratio of aluminum liquid to slag remover is 500:1;

[0152] 22 kg of mixed powder was placed in the cooled aluminum liquid and stirred by electromagnetic stirring equipment for 20 minutes and filtered. The filtrate was placed in a 10-head crystallizer for horizontal continuous casting. The effective crystallization zone height of the crystallizer was 15 mm, the cooling water inlet temperature was 25 ° C, the outlet water temperature was 40 ° C, the water pressure was 0.02 MPa, and the horizontal continuous casting speed was 900 mm / min to obtain round wire rods with a diameter of 15 mm.

[0153] S4: homogenizing the round wire rod at 550°C for 4h;

[0154] The round wire rod after homogenization is subjected to peeling at a peeling speed of 17 m / min;

[0155] The peeled round wire rod is cleaned and dried, and then extruded into plates and strips through a continuous extruder. The continuous extrusion temperature is controlled at 450°C, and the extrusion wheel speed is 10rpm. Finally, the extruded plate and strip products are rolled up using a constant tension winding device. The die mouth is equipped with a heat preservation furnace, and the furnace temperature is controlled at 350°C. Finally, after rolling, a coil of aluminum-based silicon carbide composite material is obtained.

[0156] Example 3

[0157] S1: placing silicon carbide particles (average particle size of 5 μm) in a silicon carbide cleaning agent for preliminary cleaning for 20 minutes, then ultrasonically cleaning for 30 minutes, placing the silicon carbide particles in flowing pure water, and repeatedly rinsing to remove surface residues to obtain clean silicon carbide particles;

[0158] The cleaned silicon carbide particles were immersed in a 45% hydrochloric acid solution for 25 minutes for acid activation;

[0159] After the acid-activated silicon carbide was washed with pure water several times, it was immersed in palladium water for 50 minutes.

[0160] The palladium water includes 5ppm colloidal palladium and 45% hydrochloric acid solution, and the volume ratio of the colloidal palladium to the hydrochloric acid solution is 1:1;

[0161] The silicon carbide particles on which the palladium catalyst layer is deposited are immersed in a chemical copper plating solution for 30 minutes, and after the immersion is completed, they are washed with pure water for multiple times to obtain copper-plated silicon carbide particles;

[0162] The chemical copper plating solution includes 3 g / L copper sulfate, 5% formaldehyde, 20 g / L potassium sodium tartrate and 1 g / L EDTA-2Na.

[0163] S2: Pre-treatment of mixing and dispersing the copper-plated silicon carbide particles (21 kg) and aluminum powder (3 kg, with an average particle size of 7 μm) at a mass ratio of 7:1 to obtain 24 kg of mixed powder;

[0164] S3: Weigh 76 kg of aluminum alloy ingot, place the aluminum alloy ingot in a melting furnace, melt it at 770° C., and after the aluminum ingot is completely melted into aluminum liquid, cool it to 740° C. to obtain aluminum liquid;

[0165] Argon was introduced to stir and degas the aluminum liquid for 30 minutes at a stirring speed of 400 r / min, and then 152 g of slag remover sodium fluoride was added for refining and deslagging. The mixture was allowed to stand for 20 minutes and then cooled to 660°C.

[0166] Among them, the mass ratio of aluminum liquid to slag remover is 500:1;

[0167] 24 kg of mixed powder was placed in the cooled aluminum liquid and stirred by electromagnetic stirring equipment for 20 minutes and filtered. The filtrate was placed in a 10-head crystallizer for horizontal continuous casting. The effective crystallization zone height of the crystallizer was 15 mm, the cooling water inlet temperature was 25 ° C, the outlet water temperature was 40 ° C, the water pressure was 0.02 MPa, and the horizontal continuous casting speed was 900 mm / min to obtain round wire rods with a diameter of 12 mm.

[0168] S4: homogenizing the round wire rod at 500°C for 2h;

[0169] The round wire rod after homogenization is subjected to peeling at a peeling speed of 18 m / min;

[0170] The peeled round wire rod is cleaned and dried, and then extruded into plates and strips through a continuous extruder. The continuous extrusion temperature is controlled at 400°C, and the extrusion wheel speed is 20rpm. Finally, the extruded plate and strip products are rolled up using a constant tension winding device. The die mouth is equipped with a heat preservation furnace, and the furnace temperature is controlled at 350°C. Finally, after rolling, a coil of aluminum-based silicon carbide composite material is obtained.

[0171] Comparative Example 1

[0172] Compared with Example 1, the main difference between this comparative example is that in step S2, no aluminum powder and copper-plated silicon carbide particles are added for mixed powder dispersion pretreatment, but the copper-plated silicon carbide particles are directly mixed with the aluminum liquid in step S3, and the remaining steps and technical parameters are the same as those in Example 1.

[0173] Comparative Example 2

[0174] Compared with Example 1, the main difference between this comparative example is that in step S2, the aluminum powder and the copper-plated silicon carbide particles are mixed and dispersed in a mass ratio of 1:1 (i.e., 12 kg of copper-plated silicon carbide particles and 12 kg of aluminum powder respectively) for pretreatment, and the remaining steps and technical parameters are the same as those in Example 1.

[0175] Comparative Example 3

[0176] The main difference between this comparative example and Example 1 is that in step S4, the continuous extrusion temperature is 500° C., and the remaining steps and technical parameters are the same as those in Example 1.

[0177] Comparative Example 4

[0178] Compared with Example 1, the main difference between this comparative example is that in step S4, the continuous extrusion temperature is 350° C., and the remaining steps and technical parameters are the same as those in Example 1.

[0179] Comparative Example 5

[0180] Compared with Example 1, the main difference between this comparative example is that in step S4, the rotation speed of the extrusion wheel is 50 rpm, and the remaining steps and technical parameters are the same as those in Example 1.

[0181] Comparative Example 6

[0182] The main difference between this comparative example and Example 1 is that in step S1, the silicon carbide particles are not copper plated, but are directly mixed with aluminum powder for powder dispersion pretreatment, and the remaining steps and technical parameters are the same as those in Example 1.

[0183] Performance Testing

[0184] Tensile test: The tensile test specimens of composite materials are processed according to the standard of GB / T228-2010 "Room Temperature Tensile Test of Metallic Materials", and the carbon fiber is ensured to be located in the center of the tensile sheet.

[0185] The tensile properties of the samples were tested using a DNS100 universal testing machine at a tensile speed of 1.2 mm / min.

[0186] Fracture toughness refers to GB / T 4161-2007 "Test method for plane strain fracture toughness KIC of metallic materials".

[0187] The comparison results of the mechanical properties of the plates and strips prepared in Examples 1-3 and Comparative Examples 1-6 are shown in Table 1:

[0188] Table 1

[0189] Tensile strength MPa <![CDATA[Fracture toughness MPa·m 1 / 2 > Elongation at break % Example 1 295 6.5 8.3 Example 2 287 6.1 8.0 Example 3 290 6.3 8.1 Comparative Example 1 260 5.1 7.0 Comparative Example 2 255 4.8 6.8 Comparative Example 3 - - - Comparative Example 4 232 3.4 5.5 Comparative Example 5 268 5.7 7.3 Comparative Example 6 248 4.6 6.5

[0190] As shown in Table 1, since in step S2 of comparative example 1, no aluminum powder is added to the copper-plated silicon carbide particles for mixed powder dispersion pretreatment, the dispersibility of the copper-plated silicon carbide particles in the aluminum liquid is reduced, resulting in a decrease in the mechanical properties of the prepared plate and strip.

[0191] As shown in Table 1, in step S2 of Comparative Example 2, the aluminum powder and the copper-plated silicon carbide particles are mixed and dispersed at a mass ratio of 1:1 (i.e., 12 kg of copper-plated silicon carbide particles and 12 kg of aluminum powder) for pretreatment, and the aluminum powder content is too much, so that the relative proportion of the copper-plated silicon carbide particles in the mixture is reduced, thereby increasing the chances of contact and agglomeration between the particles, resulting in a decrease in the dispersibility of the copper-plated silicon carbide particles in the aluminum liquid, and a decrease in the mechanical properties of the prepared plate and strip.

[0192] As shown in Table 1, in step S4 of comparative example 3, the continuous extrusion temperature is 500°C, and after frictional heat generation, the temperature of the aluminum substrate increases significantly, causing partial or complete melting of the aluminum substrate, thereby failing to complete extrusion into plates and strips and unable to conduct performance testing.

[0193] As shown in Table 1, in step S4 of comparative example 4, the continuous extrusion temperature is 350°C, which is too low. The temperature of the aluminum matrix cannot reach the ideal extrusion temperature, resulting in reduced plasticity of the aluminum matrix during the extrusion process, increased extrusion force, and a significant decrease in the mechanical properties of the prepared plate and strip.

[0194] As shown in Table 1, in step S4 of comparative example 5, the rotation speed of the extrusion wheel is 50 rpm, and the extrusion speed is too fast, which causes stress in the aluminum matrix and reduces the mechanical properties of the extruded strip.

[0195] As shown in Table 1, in step S1 of comparative example 6, the silicon carbide particles are not copper plated but directly mixed with aluminum powder for dispersion pretreatment, which results in reduced dispersibility of the silicon carbide particles and reduced mechanical properties of the prepared strip.

[0196] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon carbide particle reinforced aluminum-based composite material strip, characterized in that: By mass percentage, it includes 10-25% of mixed powder and 75-90% of aluminum alloy matrix; Wherein, the mixed powder includes copper-plated silicon carbide particles and aluminum powder.

2. The silicon carbide particle reinforced aluminum-based composite material strip according to claim 1, characterized in that: The mass ratio of the copper-plated silicon carbide particles to the aluminum powder is (5-10):

1.

3. The silicon carbide particle reinforced aluminum-based composite material strip according to claim 1, characterized in that: The size of silicon carbide particles without copper plating is 3-20μm; The size of aluminum powder is 1-10μm; And / or, the aluminum alloy substrate is an aluminum alloy ingot.

4. A method for preparing a silicon carbide particle reinforced aluminum-based composite material strip according to any one of claims 1 to 3, characterized in that: The steps include: S1: performing copper plating treatment on the surface of silicon carbide particles to obtain copper-plated silicon carbide particles; S2: performing a powder mixing and dispersion pretreatment on the copper-plated silicon carbide particles and the aluminum powder to obtain a mixed powder; S3: melting the aluminum alloy ingot to obtain aluminum liquid, adding the mixed powder into the aluminum liquid for stirring, and then obtaining a round wire rod through a horizontal continuous casting process; S4: homogenizing the round wire rod and then peeling the round wire rod; cleaning and drying the peeled round wire rod, and then continuously extruding the strip to obtain a silicon carbide particle reinforced aluminum-based composite material plate.

5. The method for preparing the silicon carbide particle reinforced aluminum-based composite material strip according to claim 4, characterized in that: In step S1, the copper plating process includes the following steps: S11: degreasing the silicon carbide particles and washing them with water for multiple times to obtain clean silicon carbide particles; S12: sequentially subjecting the cleaned silicon carbide particles to acid activation, palladium catalyst layer deposition and chemical copper plating to obtain copper-plated silicon carbide particles.

6. The method for preparing the silicon carbide particle reinforced aluminum-based composite material strip according to claim 5, characterized in that: The acid activation is to soak the clean silicon carbide particles in a hydrochloric acid solution; Wherein, the concentration of the hydrochloric acid solution is 45-55%, and the acid activation time is 20-30min; And / or, the depositing of the palladium catalyst layer refers to washing the silicon carbide after acid activation treatment and then immersing it in palladium water; Wherein, the palladium water comprises 5-15 ppm of colloidal palladium and 45-55% hydrochloric acid solution; The volume ratio of colloidal palladium to hydrochloric acid solution is 1:(1-2); The immersion time in palladium water is 30-50 minutes; And / or, the chemical copper plating refers to immersing the silicon carbide particles deposited with the palladium catalyst layer in a chemical copper plating solution; Wherein, the chemical copper plating solution comprises 3-7 g / L copper sulfate, 5-15% formaldehyde, 20-30 g / L potassium sodium tartrate and 0-5 g / L EDTA-2Na; The immersion time in the chemical copper plating solution is 30-50 minutes.

7. The method for preparing the silicon carbide particle reinforced aluminum-based composite material strip according to claim 4, characterized in that: Step S3 specifically includes the following steps: S31: placing the aluminum alloy ingot in a smelting furnace for melting, and cooling the ingot after it is completely melted into aluminum liquid to obtain aluminum liquid; S32: introducing argon gas to stir and degas the aluminum liquid, then adding a slag remover to perform refining and slag removal, and standing to cool down; S33: placing the mixed powder in the cooled aluminum liquid for stirring and filtering, placing the filtrate in a crystallizer for horizontal continuous casting, and obtaining a round wire rod.

8. The method for preparing the silicon carbide particle reinforced aluminum-based composite material strip according to claim 7, characterized in that: In step S31, the melting temperature is 750-770°C; after the aluminum ingot is completely melted into aluminum liquid, the temperature is lowered to 720-740°C; And / or, in step S32, the degassing time is 20-30 min, and the stirring speed is 300-400 r / min; In step S32, the mass ratio of aluminum liquid to slag remover is 450-550:1; The slagging agent includes one or more of potassium chloride, sodium chloride, sodium fluoride or calcium fluoride; In step S32, the temperature is cooled to 630-660°C for 10-20 minutes. And / or, in step S33, the stirring refers to stirring for 10-20 min by an electromagnetic stirring device; The crystallizer is a 10-head crystallizer, the height of the effective crystallization zone of the crystallizer is 10-20 mm, the cooling water inlet temperature is ≤25°C, the outlet water temperature is ≤45°C, the water pressure is 0.01-0.03Mpa, and the horizontal continuous casting speed is 850-950mm / min; The diameter of the round wire rod is 10-15mm.

9. The method for preparing the silicon carbide particle reinforced aluminum-based composite material strip according to claim 4, characterized in that: Step S4 specifically includes the following steps: S41: performing homogenization treatment on the round wire rod; S42: peeling the round wire rod after the homogenization treatment; S43: The peeled round wire rod is cleaned and dried, and then extruded into a silicon carbide particle reinforced aluminum-based composite material plate and strip through a continuous extruder.

10. The method for preparing the silicon carbide particle reinforced aluminum-based composite material strip according to claim 9, characterized in that: In step S41, the temperature of the homogenization treatment is 500-550°C and the time is 2-4h; and / or, in step S42, the peeling speed is 16-18 m / min; And / or, in step S43, the continuous extrusion temperature is between 400-450°C, and the extrusion wheel speed is 10-20 rpm.